Visions of peace Asia and the west - Shogimen, Takashi; Spencer, Vicki A. (Justice, international law and global security, 2014)
This edited collection explores the diversity of past conceptualizations as well as the remarkable continuity in the desire for peace across global intellectual traditions. Each chapter offers a case study of a particular intellectual tradition and attempts to rehabilitate 'forgotten' conceptions of peace and reclaim its contemporary relevance